Magic or Miracle?: A Christian Apologetic Response to Current Prophetic Claims in African Congregations - Ayanyinka, Ayobami A. (Asia-Africa Journal of Mission and Ministry, 2020)
What is the singular subject that currently dominates other issues in African congregations today? What is the dilemma that has seemingly crippled and incapacitated the power of God in its manifestation freely among the believers? What is the topic that attracts attention in social media, television, radio, and newspaper reports every day in the world? It is the pursuit and clamor for a miracle. It is observed that the number of church-goers, miracle-seekers, and miracle-workers is on the increase daily in Christian gatherings. The question remains, “Magic or Miracle?” If it is a miracle that only comes from God, why the craze? The biblical account is full of God’s miracles through His prophets in the Old Testament and through Jesus Christ in the New Testament. Besides, God worked wondrously through the apostles. He is still able to do wonders in this end time. Thus, this paper is a Christian apologetic response to current prophetic claims that are associated with magic but are displayed as miracles. It significantly argues that God is not a magician and miracles do not depend on human efforts. The discourse, therefore, employs the Christian apologetical method in responding to the challenges that these misconstrued conceptions have had on African Christian congregations, with particular reference to Nigeria.
free